Ambivalensi ideologi patriarki pada serial tv populer House of the Dragon: kritik feminisme - Mandela, Fitra; Gitawati, Novi Dwi (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
This article aims to analyze the ambivalence of patriarchal ideology in the popular TV series created by HBO entitled ‘House of the Dragon’ (2022). Based on this aim, the research method which is used is qualitative method. The analysis is focused on several major characters. Feminist literary criticism is the ground theory which is used to analyze the main issue of patriarchy society in this series. As one of the primary subjects of analysis in feminist criticism, this research only tries to elaborate how critics define and see patriarchy work in general. It can be concluded that this series, on its surface, shows the practice of patriarchal society. Those practices are seen in many forms such as gender inequality, subordination, and repression toward women lead characters from male characters or society. Interestingly, at the same time the analysis also leads to a different interpretation which argues those several major characters also reflect the strategy to against the patriarchal ideology. It makes the feminist reading to this series becomes ambivalent.